Effect of human dermal allograft thickness on glenohumeral stability for superior capsular reconstruction in irreparable supraspinatus tears: A biomechanical analysis of the superior capsular reconstruction – A cadaveric study. (February 2022) - Smith, Geoffrey CS; Im, Heon Y; Lam, Patrick H
Purpose: The objective of this study was to compare the biomechanics of using a double layered human dermal allograft to a single layered human dermal allograft in superior capsular reconstruction. Methods: Five cadaveric shoulders were tested. The superior translation of the humerus and the subacromial contact pressure were measured at 0°, 30° and 60° of glenohumeral abduction in the following six conditions: (1) intact rotator cuff, (2) irreparable supraspinatus tear, (3) superior capsular reconstruction using a double layered human dermal allograft with and (4) without posterior suturing, (5) superior capsular reconstruction using a single human dermal allograft with and (6) without posterior suturing. Results: There was a significant increase in superior translation of the humerus and subacromial contact pressure when comparing torn supraspinatus to intact shoulder. All superior capsular reconstruction repairs lead to a reduction in superior translation and subacromial contact pressures compared to after the supraspinatus tear except for single layered superior capsular reconstruction repair without posterior suturing. There was no difference in superior translation and subacromial contact pressures comparing the intact shoulder to any of the superior capsular reconstruction constructs. Conclusion: Superior capsular reconstruction using a single or double layered human dermal allograft improves superior translation after supraspinatus repair. There is some biomechanical benefit of a double layered human dermal allograft technique over a single layered graft technique in superior capsular reconstruction. Level of Evidence: IV